BEHAVIORAL FACTORS INFLUENCING INVESTMENT DECISIONS: A SYSTEMATIC REVIEW USING PRISMA - Sinha, Aashna; Shunmugasundaram, V (International Journal of Accounting & Finance Review, 2023)
The purpose of this systematic review is to analyze the previous study made in the past related to an association between behavioral biases and investment decisions. This systematic review article identified 21 distinct biases affecting the investment decisions made by investors. Data were collected from 3 databases (Scopus, Taylor and Francis, and Web of Science) using PRISMA guidelines. The inclusion criteria for this systematic review were (i) publication date 2012 to 2022 (ii) published in the English language (iii) open access articles (iv) all types of documents except review articles etc. The findings of the study support that there is a significant relationship between 21 distinct behavioral biases and investment decisions. The study found there is a lack of female participants to male participants. There is a sampling bias found in many studies i.e., the studies employed non-probability techniques to collect samples. This study extends the current knowledge about the previous study being researched related to an association between behavioral biases and investment decisions. This systematic review provides a clear picture of the gaps in the previous literature. This study is helpful for researchers and academicians in understanding the biases investors undergo while making investment decisions and addressing the gaps identified related to different types of behavioral biases and areas of study that need to be explored more in near future. JEL Classification Codes: D91, G10, G4, G11, G41.